2022
DOI: 10.3390/ijerph192215074
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Phases of Employment Decision-Making and the Need for Vocational Services as a Social Determinant of the Health of Employed People Living with HIV

Abstract: (1) Background: Secure employment has been recognized as a social determinant of health for people living with HIV (PLHIV), but limited research has been conducted to understand the employment needs and vocational decision-making process of those who are employed. The purpose of this study is to examine the applicability of the client-focused considering-work model to assess the employment outcomes and employment decision-making phases of a sample of employed PLHIV. (2) Methods: This study analyzed data of 244… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Despite the potential benefits of employment, more than 41% of people living with HIV reported unemployment [32]. Some studies of employed PLHIV have found high rates of insecure work [33,34]. Rueda and colleagues found that a high level of job insecurity is significantly associated with depressive symptoms in people living with HIV [34].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the potential benefits of employment, more than 41% of people living with HIV reported unemployment [32]. Some studies of employed PLHIV have found high rates of insecure work [33,34]. Rueda and colleagues found that a high level of job insecurity is significantly associated with depressive symptoms in people living with HIV [34].…”
Section: Introductionmentioning
confidence: 99%